Old markers of social stratification in the consumer society: A new role of education - A K Mamedov; E D Korkiya; S G Malashonok (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2016)
The article considers the fundamental transformation of the role of education as a value-forming element of the cultural field in the consumer society, provides a historical overview of consumer society theories, and outlines approaches to the study of education as a social-cultural phenomenon within the market economy. The authors apply the cultural sociology approach to identify patterns of educational services consumption that allows to broaden the methodology of social stratification research; consider the theory of social inequality and the principles of social stratification; identify causes of social instability and give estimates of social inequality in consumer society. Based on the works of foreign and Russian experts the authors analyze the institutional environment of social inequality (re)production: according to the results of numerous comparative studies the key such institution is the centralized system of institutional relations in the field of education. The article considers the categories of education and training, globalization and globalism in today’s society; main aspects of the consumer society development in Russia, especially the behavior of Russian consumers in the context of global consumer trends. Thus, the authors emphasize that the consumer society in general is destructive, self-focused, however, this is a vector of global development in the capitalist countries that is impossible to deny; we are to study its trends taking into account the historical aspects of consumerism and take adequate measures to normalize social life.